BUILDING ENTREPRENUERS IN ACADEMIA: HOW EDUCATION, SOCIAL SUPPORT AND SELF-EFFICACY SHAPE INTENTIONS AMONG MALAYSIAN STUDENTS? - Hemavathi Gunasegaran; Ang Sze Ming; Loo Hui Rong, (Malaysian Journal of Business and Economics (MJBE), 2025)
This study aims to investigate the influence of entrepreneurship education, social support, and self-efficacy on entrepreneurial intentions among students in Malaysian government universities. The study focuses on understanding the role of educational initiatives in fostering student-led start-ups and their potential for contributing to Malaysia's entrepreneurial ecosystem. A quantitative, cross-sectional research design was employed, with data collected via self-administered questionnaires from 219 students enrolled in entrepreneurship programs at a Malaysian government university. The analysis was conducted using SPSS version 20. The results revealed that entrepreneurship education and self-efficacy significantly influence students’ entrepreneurial intentions. However, social support, while positively associated, did not show a statistically significant impact. These findings suggest that enhancing students’ entrepreneurial self-efficacy and exposure to entrepreneurship education can play a critical role in fostering entrepreneurial intentions. The findings offer valuable insights for educators and policymakers looking to improve entrepreneurship education programs. By focusing on enhancing self-efficacy and providing practical entrepreneurial training, universities can better equip students to meet the challenges of starting new ventures, aligning with national objectives to foster innovation and economic growth. This study adds to the growing body of knowledge on entrepreneurship education within Malaysian higher education. It highlights the crucial role of educational interventions in shaping entrepreneurial intentions and underscores the importance of focusing on self-efficacy development.